Emergent themes from a quality improvement programme for CLABSI/CAUTI prevention in ICUs amid the COVID-19 pandemic. Issue 4 (21st November 2022) - Krauss, Daniel M; Molefe, Ayrin; Hung, Louella; Hayes, Kristen; Gorman, Claudia; Latterner, Michael; Henderson, Susan; Miller, Melissa
Abstract : Objectives: Healthcare-associated infection (HAI) prevention has been difficult for healthcare providers to maintain during the COVID-19 pandemic. This study summarises themes for maintaining infection prevention activities learnt from the implementation of a quality improvement (QI) programme during the pandemic. Methods: We conducted qualitative analysis of participants' semistructured exit interviews, self-assessments on HAI prevention activities, participant-created action plans, chat-box discussions during webinars and informal correspondence. Setting: Intensive care units (ICUs) with elevated rates of central line-associated bloodstream infections (CLABSI) and/or catheter-associated urinary tract infections (CAUTI) participating in the Agency for Healthcare Research and Quality Safety Programme for ICUs: Preventing CLABSI and CAUTI. Results: Forty-nine ICU teams who participated in the programme between December 2019 and April 2021 found ways to maintain activities such as daily huddles, multidisciplinary rounds, and central line and indwelling urinary catheter monitoring despite barriers, including staff turnover, a lack of time, staff fatigue and pandemic-related guidelines limiting providers' time around patients. We use four themes to summarise the ICU teams' adaptations that allowed them to sustain infection prevention activities: (1) Units had CLABSI and CAUTI prevention teams, policies and practices established prior to the pandemic; (2) Units were flexible in their implementation of those policies and practices; (3) Units maintained consistent buy-in for and engagement in HAI prevention activities among both leadership and care teams throughout the pandemic and (4) Units looked to learn from other units in their facility and beyond. Conclusions: Future shocks such as the pandemic must be anticipated, and the healthcare system must be resilient to the resulting disruptions to HAI prevention activities. This study encountered four themes for successful maintenance of infection prevention activities during the current pandemic: the value of a pre-existing infection prevention infrastructure; a flexibility in approach; broad buy-in for maintaining QI programmes and the facilitation of idea-sharing.